Go With Your Gut: Understanding Microbiota and Prebiotics - Wendy J. Dahl; Volker Mai (EDIS)
All of us have friendly bacteria all over our bodies. A large population of bacteria lives in our gastrointestinal tract, residing mostly in the colon (large intestine). This is known as our gut microbiota. Learn more in this 2-page fact sheet written by Wendy J. Dahl and Volker Mai and published by the UF Department of Food Science and Human Nutrition, June 2011.